Interfacial engineering tailoring the dielectric behavior and energy density of BaTiO3/P(VDF-TrFE-CTFE) nanocomposites by regulating a liquid-crystalline polymer modifier structure. Issue 36 (28th August 2018) - Qian, Kun; Lv, Xuguang; Chen, Sheng; Luo, Hang; Zhang, Dou
Abstract : For the first time, the effect of a rigid-liquid-crystalline polymer modifier structure on the dielectric behavior and energy density of BaTiO3 /P(VDF-TrFE-CTFE) nanocomposites was investigated. Abstract : Dielectric polymer-based nanocomposites have attracted significant attention in recent years for energy storage applications because of their potential high permittivity and breakdown strength. The coupling effect of a nanofiller/matrix interface plays a crucial role in the dielectric and electric properties of polymer-based nanocomposites. In this paper, three kinds of side-chain liquid crystalline fluoric-polymers, denoted as P- n F ( n = 3, 5 or 7, which is the number of terminal fluoric groups), were grafted on the surface of BaTiO3 nanoparticles by a surface-initiated reversible-addition–fragmentation chain transfer polymerization method. The nanocomposite films were prepared via core–shell BaTiO3 nanoparticles dispersed in a poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene) P(VDF-TrFE-CTFE) polymer matrix. The frequency dependent dielectric properties and energy storage capability of the polymer nanocomposites were studied. The results showed that the permittivity and energy densities of the polymer nanocomposites depended on the molecular structure of the modifier, especially the number of electron-rich fluoric groups. Firstly, all modified BaTiO3 nanoparticles were homogeneously dispersed in the polymer matrix, resulting in the polymer nanocomposites presenting a higher breakdown strength compared with the unmodified BaTiO3 nanoparticles. Secondly, the changes in the nanocomposites' permittivity exhibited diversity for three modifiers due to many influential factors. Thirdly, compared with neat P(VDF-TrFE-CTFE), the discharge energy densities of the polymer nanocomposites are all significantly improved. The highest discharge energy densities of nanocomposites with 5 vol% P-3F@BT reached 14.5 J cm −3 . These findings suggest that the optimal interfacial modifier should be carefully decided by combining various properties of the nanocomposites for energy storage.